ISLAMIC FINANCE, GROWTH, AND VOLATILITY: A FRESH EVIDENCE FROM 82 COUNTRIES - Mudeer A Khattak; Noureen A. Khan (Journal of Islamic Monetary Economics and Finance, 2023)
Islamic finance has gained significant attention during the past decades. Many countries are striving to become Islamic financial hubs. The asset-backed nature of Islamic financial instruments and products adds more reliability to financial transactions. Yet, the impact of Islamic finance penetration on economic growth is unclear. While the existing studies have focused mainly on Islamic banking penetration, which is mostly centered around Muslim economies, we study the relationship considering a global sample of 82 countries, including Muslim and non-Muslim countries, from 2012-2020. We employ the System Generalized Method of Moments estimator for potential issues of endogeneity, heterogeneity, and serial correlation. Employing the novel Islamic finance development indicator by Thomson routers, we find that Islamic finance stimulates the overall economy and lessens volatility. Digging deep into the study, we find that this impact is more prominent in Muslim majority countries. These findings are robust to different econometric estimators and sample specifications. Since integrating Islamic financial principles into the country's overall financial system brings extra growth and lower economic volatility, it is recommended that the Islamic banking sector, Islamic insurance sector, Islamic money, and capital market instruments be expanded to boost overall economic growth and control volatility.